(untitled) (Journal of Numerical Optimization and Technology Management, 2023)
The name "metaverse" is a combination of the words "meta" and "universe." The metaverse refers to both present and future digital platforms that are interconnected and focuses on virtual and augmented reality. The purpose of this research to identify the drivers of the future of metaverse in tourism and study the future trend of metaverse in tourism. The target respondents are select and cover mainly by developers and organizational users of metaverse in tourism. In the conduct of this research, both quantitative and qualitative research methods have been taken, and both methods will be apply in the process of the data analysis and data interpretation. In this research, the STEEPV analysis is apply. The STEEPV technique will be utilized in order to determine or identify all the drivers of metaverse in tourism. Data from the questionnaire are analyze using "Social Science Statistics Package" (SPSS). It shows the result of drivers of metaverse in tourism portable devices in the second phase of the research with impact-uncertainty analysis. The top two drivers are “government policy in digitizing the nation” and “technology reliability”. Four different scenarios have been formed based on the top two drivers chosen from the impact-uncertainty analysis. These four alternate scenarios reflect the four potential outcomes between 2022 and 2032. Hence, this research can help future researchers and developers increase their awareness of adopting the metaverse in tourism sector in future. A further explanation of the findings has been given in the discussion.